Keputusan Investasi Pada Industri Logistik & Pengiriman Dengan Menggunakan Metode Capital Asset Pricing Model (CAPM): Periode (2022) - Permatasari, Indah (Politeknik Negeri Ambon, 2023)
This journal discusses investment decisions in the logistics & deliveries industry using the Capital Asset Pricing Model (CAPM) method. This research was conducted to determine investment decisions using a sample of 7 companies listed on the Indonesian stock exchange. The primary method of data collection for this research is quantitative research, which involves collecting secondary data from required documents and reports. Viewed from historical data for the 2022 period per month from January - December 2022. This research applies the Capital Asset Pricing Model (CAPM) method to determine companies that have a risk-free rate of return as a consideration in making investment decisions.